Early Experience Using an Online Reporting System for Interventional Radiology Procedure-Related Complications Integrated with a Digital Dictation System - Gupta, Sanjay (Springer-Verlag, 2010)
The absence of user-friendly systems for reporting complications is a major barrier to improving quality assurance (QA) programs in interventional radiology (IR) services. We describe the implementation of a QA application that is completely integrated with the radiology dictation system. We implemented an IR QA process as a module within the electronic medical record and radiologist dictation system applications used at our institution. After a radiologist completes a dictation, he or she must select from a drop-down list of complications before proceeding to the next case. Delayed QA events can be entered using the same applications. All complication entries are sent to a database, which is queried to run reports. During the study period, all the 20,034 interventional procedures were entered in the QA database, 1,144 complications were reported, 110 (9.6%) of which were classified as major. Although majority of the complications (996) were entered at the time of dictation, 148 complications (12.9%) were entered afterwards. All major complications were referred to the IR peer review committee, and 30 of these were discussed in the morbidity and mortality meetings. We studied post-lung-biopsy pneumothorax and chest tube rates and initiated a quality improvement process based on the results.The integration of the IR QA reporting system into the workflow process and the mandatory requirements for completion has the potential to minimize the work effort required to enter complication data, and improve participation in the QA process.